Stressed, not frozen: The federal funds market in the financial crisis - Gara Afonso; Anna Kovner; Antoinette Schoar (Federal Reserve Bank of New York, 2010)
This paper examines the impact of the financial crisis of 2008, specifically the bankruptcy of Lehman Brothers, on the federal funds market. Rather than a complete collapse of lending in the presence of a market-wide shock, we see that banks became more restrictive in their choice of counterparties. Following the Lehman bankruptcy, we find that amounts and spreads became more sensitive to a borrowing bank's characteristics. While the market did not contract dramatically, lending rates increased. Further, the market did not seem to expand to meet the increased demand predicted by the drop in other bank funding markets. We examine discount window borrowing as a proxy for unmet fed funds demand and find that the fed funds market is not indiscriminate. As expected, borrowers who access the discount window have a lower return on assets. On the lender side, we do not find that the characteristics of the lending bank significantly affect the amount of interbank loans it makes. In particular, we do not find that worse performing banks began hoarding liquidity and indiscriminately reducing their lending.
Keywords: G21; G01; D40; E40; 330; Fed funds; financial crisis; liquidity; interbank lending; hoarding; Finanzmarktkrise; Geldmarkt; Insolvenz; Zentralbank; Zinspolitik; USA